The Role of Digitalization on the Development of MSME in Business Actors Bangka Typical Souvenirs in Pangkalpinang City - Rimadhini, Adilla Naura; Mukhlis, Imam (Trunojoyo University of Madura, 2025)
Rapid technological advancements occur in almost all countries, including Indonesia.One field affected by technological progress is the economy. Indonesia’s economic strength includes the continuous development of Micro, Small, and Medium Enterprises (MSMEs). Digitalization plays a significant role in advancing MSMEs and thus the economy. This study aims to analyze the role of digitalization in the development of MSMEs among traditional snack business owners in Pangkalpinang City. Sampling was done using purposive sampling technique with a population of traditional snack business owners, particularly those dealing with sea products, with a sample size of 70 respondents. Data collection was conducted through an online questionnaire using Google Form platform. The data analysis method employed in this study is Partial Least Square using SmartPLS software, utilizing both outer and inner models. Research findings indicate that digital marketing, financial literacy, and financial technology have a positive and significant impact on the development of MSMEs among traditional snack business owners in Pangkalpinang City.